DEVELOPMENT OF MANAGEMENT TEAM USING GAMIFICATION IN THE GOVERNMENT OF INDONESIA - Agusta Dirga Saputra; Gunawan Wang (INFOKUM, 2022)
This study aims to develop gamification-based team management software using the Mechanic, Dynamic, Aesthetic and Waterfall Framework frameworks and test its effectiveness in case studies at the Ministry of Communication and Informatics. The software development methodology used is a waterfall, integrating gamification elements such as a points system, leaderboard, and rewards to improve team motivation and performance. This research uses qualitative and quantitative approaches to analyze the effectiveness of the software developed. The results showed that this gamification-based team management software succeeded in significantly increasing team motivation and performance and helping to achieve the targets set in the project. This research makes an important contribution to gamification-based team management software development and can be applied to other organizations to improve team performance.